2020
DOI: 10.1002/fsn3.1894
|View full text |Cite
|
Sign up to set email alerts
|

In vitro probiotic screening and evaluation of space‐induced mutant Lactobacillus plantarum

Abstract: Probiotics are a group of bacteria that contribute to maintenance or promotion of human health, as they can enhance immune system (Albuquerque-Souza et al., 2019), alleviate food allergies (Irina, Ceuppens, Seys, Petrova, & Sarah, 2018), and prevent irritable bowel syndrome (Ashton, Malwina, & Davinder, 2018). A desirable probiotic has one or more of the following properties: (a) high resistance to low pH and bile salt during digestion (Jia, 2010), (b) strong adherence to the intestinal cells for colonization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…For example, a previous report found that Aspergillus fumigatus isolated from the International Space Station produced more fumigaclavine A than the reference strain, which was caused by a specific frameshift mutation in the prenyl transferase-encoding gene, fgaPT1 . Another study reported that a space exposed mutant, Lactiplantibacillus plantarum SS18-50, had stronger acid tolerance, bile salt tolerance, and antibacterial activity compared with the wild type; and the fermented milk produced by this strain had a higher viscosity compared with that of the control . These studies showed that space mutagenesis is a good strategy for microbial breeding and strain improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a previous report found that Aspergillus fumigatus isolated from the International Space Station produced more fumigaclavine A than the reference strain, which was caused by a specific frameshift mutation in the prenyl transferase-encoding gene, fgaPT1 . Another study reported that a space exposed mutant, Lactiplantibacillus plantarum SS18-50, had stronger acid tolerance, bile salt tolerance, and antibacterial activity compared with the wild type; and the fermented milk produced by this strain had a higher viscosity compared with that of the control . These studies showed that space mutagenesis is a good strategy for microbial breeding and strain improvement.…”
Section: Introductionmentioning
confidence: 99%
“…18 Another study reported that a space exposed mutant, Lactiplantibacillus plantarum SS18-50, had stronger acid tolerance, bile salt tolerance, and antibacterial activity compared with the wild type; and the fermented milk produced by this strain had a higher viscosity compared with that of the control. 19 These studies showed that space mutagenesis is a good strategy for microbial breeding and strain improvement. To our knowledge, only few studies investigated the potential of space mutagenesis in improving the properties of dairy starter cultures and the quality of their fermented products produced.…”
Section: Introductionmentioning
confidence: 99%
“…For example, after 44 days of ight with the FOTON-M4 satellite, the nitrogen-transforming activity of broad-spectrum nitrogen-cycling microorganisms was signi cantly increased (Lindeboom et al 2018). The mutant Lactobacillus plantarum SS18-50 produced by spatial mutagenesis has the strongest probiotic and bacteriostatic properties (Wang et al 2020). A genetically engineered Escherichia coli of recombinant human interferon α1b was processed on the Shenzhou-8 spacecraft and tracked in space, resulting in ve mutant strains that tripled the target protein production (Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus plantarum is a Gram-positive anaerobic or facultative anaerobic Lactobacillus, which is widely distributed in nature, especially in various fermented foods, dairy products, fermented dough and so on [1] . The optimum temperature range is generally 30 °C to 35 °C.…”
Section: Introductionmentioning
confidence: 99%